2018
DOI: 10.1177/1545968318818904
|View full text |Cite
|
Sign up to set email alerts
|

Response Heterogeneity With Exercise Training and Physical Activity Interventions Among Persons With Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a heterogeneous disease, both in its pathology and symptomology. This poses a challenge for the medical management and rehabilitation of MS; however, physical activity and exercise training are rehabilitation approaches that have demonstrated beneficial effects on many of the burdensome consequences of MS such as mobility impairment and fatigue. Given the heterogeneous course of MS, it is possible that outcomes of physical activity and exercise training interventions demonstrate hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 74 publications
(124 reference statements)
1
18
1
Order By: Relevance
“…Several interventions, including exercise training, have been developed to reduce fatigue by improving physical behavior, but the results are insufficient [9]. One explanation for this is that in MS patients, not only the general symptomology is heterogeneous, but also the response to exercise seems highly heterogeneous [10, 11]. As a consequence, considerable variability might be present in the symptoms of fatigue, PB, and in their interaction across and within patients [12, 13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several interventions, including exercise training, have been developed to reduce fatigue by improving physical behavior, but the results are insufficient [9]. One explanation for this is that in MS patients, not only the general symptomology is heterogeneous, but also the response to exercise seems highly heterogeneous [10, 11]. As a consequence, considerable variability might be present in the symptoms of fatigue, PB, and in their interaction across and within patients [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that patients with similar levels of fatigue are likely to show varying PB, and that interventions do not match PB starting levels of all patients. More insight in the variability of PB in fatigued MS patients is needed, as better understanding will contribute to the development of more personalized interventions and improve disease management in rehabilitation [10]. To date, the heterogeneity of PB at the start of interventions for fatigued MS patients has not been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Medical care that is specially tailored to the patient improves the course of the disease by reducing side effects to a minimum. In addition, the acceptance of the medication is increased, which in turn improves the effect of the medication (55)(56)(57)(58).…”
Section: Integration Of the Patient's Perspectivementioning
confidence: 99%
“…A recent published review concluded that response heterogeneity following exercise intervention still remains understudied among pwMS. Since many studies that present individual data were characterized by small samples, the value of information is limited [24].…”
Section: Introductionmentioning
confidence: 99%
“…In order to give more detailed, individualized training and rehabilitation recommendations for pwMS, it remains crucial to identify predictors influencing training response in larger cohorts [6,24]. Therefore, this secondary analysis of two RCTs in 131 pwMS examines participants' characteristics (gender, age, MS phenotype, neurological disability, baseline fatigue and baseline fitness) and the training modality as potential influencing factors on the training response following HIIT vs. MCT.…”
Section: Introductionmentioning
confidence: 99%